Challanges Prepupillary Iris Claw Implantation In Irregular-Shaped Pupil: Poster Presentation - Case Report - Resident - Rusli, Richardo; Umboh, Roy (Majalah Oftalmologi Indonesia, 2023)
Introduction : For decades secondary implants carry a greater risk of high complications. The iris claw technique is popular because of the safe and fast IOL implantation. But, in this case there is a difficulty where the pupil shape is irregular so that it is a challenge for enclavation the haptic on the prepupillary iris. Case Illustration : A man, 39 YO, came with complaints of blurred right eye after surgery on the right eye 6 months ago. Vision 1/60 with pinhole reaching 20/70, , deep anterior chamber with VH 4, positive iris tremulans, with irregular shape in temporal regio where is the main port where the first operation was performed, not centrally located pupil. There was no intraocular lens found in the lens. The patient was planned for the installation of a Secondary IOL in the right eye with a prepupillary iris claw and endodiathermal pupilloplasty to returns the pupil to the central position. One day after surgery, visual acuity was 1/300, IOP was 30 mmHg and the descment fold. The anterior chamber is difficult to evaluate. 4 weeks after surgery, Vision was 20/70, cornea was clear and IOP was 17mmHg without the need for return surgery. Discussion : Until now, there is still no consensus regarding the best management options to correct aphakia without adequate lens capsule support. Endothermal diathermy pupilloplasty itself aims to create and maintain an appropriate pupil size. Conclusion : Even though there are complications, the installation of the iris claw on the prepupillary is still a safe technique for aphakic correction.